Characteristics of participants consenting versus declining follow-up for up to 10 years in a randomized clinical trial. (December 2015) - Sheffet, Alice J; Voeks, Jenifer H; Mackey, Ariane; Brooks, William; Clark, Wayne M; Hill, Michael D; Howard, Virginia J; Hughes, Susan E; Tom, MeeLee; Longbottom, Mary E; Brott, Thomas G
Background: With patients living a decade or longer post-procedure, long-term data are needed to assess the durability of carotid artery stenting versus carotid endarterectomy. Identifying characteristics of those consenting or declining to continue in long-term follow-up may suggest strategies to improve retention in clinical trials. Purpose: This report describes differences between patients choosing or declining to continue follow-up for up to 10 years in the Carotid Revascularization Endarterectomy versus Stenting Trial. Methods: Following completion of the primary outcome, patients who were in active Carotid Revascularization Endarterectomy versus Stenting Trial follow-up were asked to continue beyond their original 4-year commitment for a maximum of 10 years. The characteristics of those who consented were compared with those who declined. Univariate and multivariable logistic regression were used for analysis, and backwards stepwise logistic regression (the most parsimonious model) was used to determine the factors associated with continuation. Results: Of the 1921 active Carotid Revascularization Endarterectomy versus Stenting Trial participants for whom consent to extend follow-up was requested, 1695 (88%; mean age: 68.4) consented; 226 (12%; mean age: 69.6) declined. Of those who did not consent versus those who consented, 66% versus 48% were symptomatic at baseline (p < 0.0001), at follow-up 28% versus 20% were smokers (p = 0.009), 85% versus 90% were hypertensive (p = 0.01), and 84% versus 94% were dyslipidemic (p < 0.0001). Additional factors that differed between those who did not consent and those who consented included the mean number of years in the study at time of consent (4.8 years vs 3.7 years (p = <0.0001)) and patients from sites that enrolled <30 patients compared to sites randomizing 30 or more (70% vs 52% (p < 0.0001)). Multivariable logistic regression indicated that those with lesser odds of consenting to the extended follow-up were older (odds ratio: 0.80; 95% confidence interval: 0.67, 0.96), more likely to be symptomatic (odds ratio: 0.58; 95% confidence interval: 0.42, 0.80), smokers (odds ratio: 0.48; 95% confidence interval: 0.34, 0.70), were in the study 5+ years versus <3 (odds ratio: 0.21; 95% confidence interval: 0.13, 0.34), and at a site that randomized <30 patients (odds ratio: 0.46; 95% confidence interval: 0.33, 0.63), while patients with dyslipidemia at follow-up had increased odds of consenting (odds ratio: 2.28 (1.47, 3.54)). Conclusion: Symptomatic status, increasing age, randomized at lower volume centers, and longer time in follow-up were associated with reduced odds of consenting to long-term follow-up. Identifying factors associated with reduced willingness to extend participation long-term can suggest targeted strategies to improve retention in future clinical trials.